Nuclear poly(A)-binding protein aggregates misplace a pre-mRNA outside of SC35 speckle causing its abnormal splicing. Issue 22 (9th August 2016) - Klein, Pierre; Oloko, Martine; Roth, Fanny; Montel, Valérie; Malerba, Alberto; Jarmin, Susan; Gidaro, Teresa; Popplewell, Linda; Perie, Sophie; Lacau St Guily, Jean; de la Grange, Pierre; Antoniou, Michael N.; et al.
Abstract: A short abnormal polyalanine expansion in the polyadenylate-binding protein nuclear-1 (PABPN1) protein causes oculopharyngeal muscular dystrophy (OPMD). Mutated PABPN1 proteins accumulate as insoluble intranuclear aggregates in muscles of OPMD patients. While the roles of PABPN1 in nuclear polyadenylation and regulation of alternative poly(A) site choice have been established, the molecular mechanisms which trigger pathological defects in OPMD and the role of aggregates remain to be determined. Using exon array, for the first time we have identified several splicing defects in OPMD. In particular, we have demonstrated a defect in the splicing regulation of the muscle-specific Troponin T3 ( TNNT3 ) mutually exclusive exons 16 and 17 in OPMD samples compared to controls. This splicing defect is directly linked to the SC35 (SRSF2) splicing factor and to the presence of nuclear aggregates. As reported here, PABPN1 aggregates are able to trap TNNT3 pre-mRNA, driving it outside nuclear speckles, leading to an altered SC35-mediated splicing. This results in a decreased calcium sensitivity of muscle fibers, which could in turn plays a role in muscle pathology. We thus report a novel mechanism of alternative splicing deregulation that may play a role in various other diseases with nuclear inclusions or foci containing an RNA binding protein.